Essentials of negotiation. - Lewicki, Roy J.; Barry, Bruce, 1958-; Saunders, David M. (McGraw Hill, 2024)
'Essentials of Negotiation' is a condensed version of the main text, 'Negotiation'. It explores the major concepts and theories of the psychology of bargaining and negotiation, and the dynamics of interpersonal and inter-group conflict and its resolution. Several chapters from the main text have been condensed for this volume. These condensed chapters have shifted from a more research-oriented focus to a more fundamental focus on issues such as critical negotiation sub processes, multiparty negotiations, and the influence of international and cross-cultural differences on the negotiation process.